(untitled) (Journal of Nepal Geological Society, 2004)
The surface and subsurface water of the Kathmandu valley has been severely contaminated by various pollutants since the last fifteen years. Many factors have played their role in polluting the rivers and wells of the valley. The water quality monitoring of the Bagmati River and its tributaries revealed a strong seasonal variation. Ammonia, nitrate, phosphate, dissolved Oxygen, biological oxygen demand, chemical oxygen demand, and total suspended solids are the main determinants of river water pollution. Similarly, the water samples drawn from various deep tubewells, shallow wells, and springs reveal a remarkable contamination of groundwater. Most of the deep tubewells of the Kathmandu valley consist of a greater amount of ammonia and iron as well as higher turbidity and colour values than those of the WHO guideline values. The water analysis data of the Bagmati River and its tributaries show an increasing contamination trend in the densely populated areas. Minbhawan, The Hanumante Khola, Dhobi Khola, Tukucha, Teku, and the Bishnumati Khola are comparatively more polluted while the Nakhu Khola and Balkhu Khola are less contaminated. The quality of groundwater is also deteriorating day by day due to the inadequate precautions and facilities to treat sewage and wastewater.